CURRENT STATE AND PROSPECTS OF DEVELOPMENT OF THE WORLD MARKET OF THE LIQUEFIED NATURAL GAS - Natalia V. Lazareva; Victor A. Fursov; Irina N. Lavrinets (Вестник Северо-Кавказского федерального университета, 2022)
In article the analysis of the markets of the liquefied natural gas where the main tendencies of develop- ment of branch of LNG and where the assessment is given are designated is carried out what place in this niche of gas sector of the world market can occupy the Russian Federation.